Gender relations in global agri-food value chains – a review - Schumacher, Kim Philip (DIE ERDE – Journal of the Geographical Society of Berlin, 2014)
This article reviews the research literature on gender relations in global agri-food value chains. The main focus is on the production side in countries of the Global South, with most examples from sub-Saharan Africa. After a short presentation of the underlying concepts and a review of the existing research literature, an outline is given of the major insights the analysis of gender issues in global value chains has offered. What is striking is the heterogeneity of the findings and proposed actions, as well as the scarcity of conceptual approaches that would integrate gender analyses further into the concept of global value chains.